Effects of varying presentation time on long-term recognition memory for scenes: Verbatim and gist representations. - Ahmad, Fahad; Moscovitch, Morris; Hockley, William (Memory & Cognition, 2017)
Konkle, Brady, Alvarez and Oliva ( Psychological Science, 21, 1551-1556, 2010) showed that participants have an exceptional long-term memory (LTM) for photographs of scenes. We examined to what extent participants' exceptional LTM for scenes is determined by presentation time during encoding. In addition, at retrieval, we varied the nature of the lures in a forced-choice recognition task so that they resembled the target in gist (i.e., global or categorical) information, but were distinct in verbatim information (e.g., an 'old' beach scene and a similar 'new' beach scene; exemplar condition) or vice versa (e.g., a beach scene and a new scene from a novel category; novel condition). In Experiment 1, half of the list of scenes was presented for 1 s, whereas the other half was presented for 4 s. We found lower performance for shorter study presentation time in the exemplar test condition and similar performance for both study presentation times in the novel test condition. In Experiment 2, participants showed similar performance in an exemplar test for which the lure was of a different category but a category that was used at study. In Experiment 3, when presentation time was lowered to 500 ms, recognition accuracy was reduced in both novel and exemplar test conditions. A less detailed memorial representation of the studied scene containing more gist (i.e., meaning) than verbatim (i.e., surface or perceptual details) information is retrieved from LTM after a short compared to a long study presentation time. We conclude that our findings support fuzzy-trace theory.